Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Microbacterium enclense sp nov., isolated from sediment sample - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel bacterium (strain NIO-1002(T)) belonging to the genus Microbacterium was isolated from a marine sediment sample in Chorao Island, Goa Province, India. Its morphology, physiology, biochemical features and 16S rRNA gene sequence were characterized. Cells of this strain were Gram-stain-positive, non-motile, non-spore-forming rods that formed yellow-pigmented colonies. It grew in 0-12 % (w/v) NaCl and at 25-37 degrees C, with optimal growth at 30 degrees C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1002(T) is associated with members of the genus Microbacterium, with highest sequence similarity with Microbacterium hominis CIP 105731(T) (98.1%) and Microbacterium testaceum KCTC 9103(T) (98.0 %). Within the phylogenetic tree, this novel strain shared a branching point with M. hominis CIP 105731(T). The DNA G+C content was 66.5 mol% and DNA DNA hybridization relatedness between NI-1002(T), M. hominis CIP 105731(T) and M. testaceum KCTC 9103(T) was 39.0 +/- 2.0 % and 41.0 +/- 2.0 %, respectively. The major fatty acids were ai-C-15:0, i-C-16:0 and al-C-17:0 and the diamino acid in the cell-wall peptidoglycan of NIO-1002(T) was lysine. Data obtained from DNA-DNA hybridization and chemotaxonomic phenotypic analysis support the conclusion that strain NIO-1002(T) represents a novel species within the genus Microbacterium. The name Microbacterium enclense sp. nov. is proposed, with NIO-1002(T) (=NCIM 5454(T)=DSM 25125(T)=CCTCC AB 2011120(T)) as the type strain.

Reclassification of bacillus isronensis shivaji et al. 2009 as solibacillus isronensis comb. nov and emended description of genus solibacillus krishnamurthi et al. 2009 - Mual, Poonam; Singh, Nitin Kumar; Verma, Ashish; Schumann, Peter; Krishnamurthi, Srinivasan; Dastager, Syed Gulam; Mayilraj, Shanmugam (International Journal of Systematic and Evolutionary Microbiology, 2016)
An investigation into the taxonomic position of Bacillus isronensis MTCC 7902(T) revealed that the strain shares a common phylogenetic lineage with Solibacillus silvestris MTCC 10789(T). It displays considerable overlap in phenotypic properties with the genus Solibacillus, including endospore shape and position, oxidase and catalase activities, presence of iso-C-15 : 0, C-16 : (1)omega 7c alcohol and iso-C-17 : 1 omega 7c as major cellular fatty acids, A4 alpha-type cell-wall peptidoglycan, polar lipids and menaquinone pattern. These features reinforce the findings of molecular phylogenetic analyses based on 16S rRNA gene, gyrB gene and 16S-23S internal transcribed spacer (ITS) region sequences and, in line with the recommendations of Kampfer et al. [Int J Syst Evol Microbiol 56 (2006), 781-786], provide justification for the transfer of Bacillus isronensis from the genus Bacillus to Solibacillus as Solibacillus isronensis comb. nov. The type strain is B3W22(T) (=MTCC 7902(T) =DSM 21046(T) =JCM 13838(T)). An emended description of the genus Solibacillus is also provided.

Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.

Examination into the taxonomic position of Bacillus thermotolerans Yang et al., 2013, proposal for its reclassification into a new genus and species Quasibacillus thermotolerans gen. nov., comb. nov. and reclassification of B. encimensis Dastager et al., - Verma, Ashish; Pal, Yash; Khatri, Indu; Ojha, Anup Kumar; Gruber-Vodicka, Harald; Schumann, Peter; Dastager, Syed Gulam; Subramanian, Srikrishna; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
Two novel Gram-staining positive, rod-shaped, moderately halotolerant, endospore forming bacterial strains 5.5LF 38TD and 5.5LF 48TD were isolated and taxonomically characterized from a landfill in Chandigarh, India. The analysis of 16S rRNA gene sequences of the strains confirmed their closest identity to Bacillus thermotolerans SgZ-8T with 99.9% sequence similarity. A comparative phylogenetic analysis of strains 5.5LF 38TD, 5.5LF 48TD and B. thermotolerans SgZ-8(T) confirmed their separation into a novel genus with B. badius and genus Domibacillus as the closest phylogenetic relatives. The major fatty acids of the strains are iso-C15:0 and iso-C16:0 and MK-7 is the only quinone. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The digital DNA-DNA hybridization (DDH) and ortho average nucleotide identity (ANI) values calculated through whole genome sequences indicated that the three strains showed low relatedness with their phylogenetic neighbours. Based on evidences from phylogenomic analyses and polyphasic taxonomic characterization we propose reclassification of the species B. thermotolerans into a novel genus named Quasibacillus thermotolerans gen. nov., comb. nov with the type strain SgZ-8(T) (=CCTCC AB2012108(T)=KACC 16706(T)). Further our analyses also revealed that B. encimensis SGD-V-25(T) is a later heterotypic synonym of Bacillus badius DSM 23(T).

Investigation into the taxonomy of “ B. aminovorans” and its reclassification to the genus Domibacillus as Domibacillus aminovorans sp. nov. - Verma, Ashish; Ojha, Anup Kumar; Pal, Yash; Kumari, Parveen; Schumann, Peter; Gruber-Vodicka, Harald; Dastager, Syed Gulam; Natarajan, Ramesh Kumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
The species "Bacillus aminovorans" was categorized as species Incertae Sedis meaning taxa with uncertain taxonomic position because of insufficient description of phenotypic properties and lack of understanding of its phylogenetic relationship (Claus and Berkeley [5]). In this study two strains "B. aminovorans" DSM 1314T and DSM 4337 were phenotypically and phylogenomically analyzed. The strains are Gram-staining-positive, spore forming rods and unable to utilize/ferment most of the sugars tested except glucose. The major fatty acids are anteiso-C15:0 and iso-C15:0. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and an aminophosphoglycolipid. The cell wall peptidoglycan is of A1γ type with meso-Dpm as the diamino acid. The menaquinone type present is MK-6. The G+C content of the genomic DNA of the type strain is 40.8mol%. These characteristics were found to be in line with description of the genus Domibacillus. Moreover phylogenetic analysis based on 16S rRNA gene sequence retrieved "B. aminovorans" within the genus Domibacillus with D. antri XD 80T as the closest relative. Additionally genome sequencing of the strains and their comparison with whole genome sequences of other Domibacillus spp. confirmed their distinctiveness and separate species status within the genus based on parameters of genome to genome distance calculator (GGDC) and average nucleotide identity (ANI) values. Therefore a novel species Domibacillus aminovorans sp. nov. (DSM 1314T =LMG 16796T) is proposed.
Keywords: 16S rRNA; Domibacillus aminovorans; MALDI-TOF; ``Bacillus aminovorans''

Microbacterium enclense sp. nov., isolated from sediment sample (vol 65, pg 2064, 2015) - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed G. (International Journal of Systematic and Evolutionary Microbiology, 2019)

Taxonomic insights into the phylogeny of Bacillus badius and proposal for its reclassification to the genus Pseudobacillus as Pseudobacillus badius comb. nov. and reclassification of Bacillus wudalianchiensis Liu et al. - Verma, Ashish; Pal, Yash; Ojha, Anup Kumar; Kumari, Munesh; Khatri, Indu; Rameshkumar, N.; Schumann, Peter; Dastager, Syed G.; Mayilraj, Shanmugam; Subramanian, Srikrishna; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2019)
The species Bacillus badius is one of the oldest members of the genus Bacillus isolated from faeces of children and was classified based on its ability to form endospores [8]. In 16S rRNA gene sequence and phylogenetic analysis, Bacillus badius DSM 23(T) shared low similarity (93.0%) and distant relationship with B. subtilis, the type species of the genus Bacillus indicating that it does not belong to this genus. Additional strains of the species, B. badius DSM 5610, DSM 30822 and B. encimensis SGD-V-25 (which has been recently reclassified as a member of this species) were included in the study to consider intraspecies diversity. Detailed molecular phylogenetic and comparative genome analysis clearly showed that the strains of B. badius were consistently retrieved outside the cluster of Bacillus sensu stricto and also distantly related to the genera Domibacillus and Quasibacillus. Further, the data from biochemical reactions (inability to ferment most carbohydrates), polar lipids profile (presence of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an aminophosphoglycolipid) and fatty acids supported the molecular analysis. Thus the four B. badius strains; DSM 23(T), DSM 5610, DSM 30822 and SGD-V-25 displayed sufficient demarcating phenotypic characteristics that warrant their classification as members of a novel genus and single species, for which the name Pseudobacillus badius gen. nov. comb. nov. is proposed with Pseudobacillus badius DSM 23(T) (= ATCC 14574(T)) as the type strain. Additionally, based on our findings from phenotypic, chemotaxonomic and genotypic parameters, Bacillus wudalianchiensis DSM 100757(T) was reclassified as Pseudobacillus wudalianchiensis comb. nov. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: 16S rRNA; Bacillus; Bacillus wudalianchiensis; Fatty acids; polar lipids; Pseudobacillus